Kadazan-Dusun Participation In Positive Youth Development Program In Sabah - Getrude Cosmas; Abd Hakim Mohad @ Mohammad Ramli; Shazia Iqbal Hashmi; Walton Wider (Institut Penyelidikan Pembangunan Belia Malaysia, 2024)
This study examines the involvements of Kadazan-Dusun youths from Buayan village in youth development program. The program was implemented with objectives to enhance their soft-skills by using structured group activities. The program focused on seven components of soft skills (i.e., time management, social competence, achievement motivation, intellectual flexibility, leadership, emotional control and self-confidence). Altogether, 21 rural youths participated in this study who were divided into two groups, (n=7) involved in structured group activities and (n=14) were not involved in structured group activities). A set of questionnaires which consists of two sections were used to measure the demographic profiles and the seven components of soft skills by using 16 items which were adapted from the Life Effectiveness Scale (Neil, 2005). Various activities such as motivational talks, future career talks, youth discussions, motivational song and games were implemented as a part of youth development program. It was assumed that there would be differences in each of the seven components of soft skills between the two groups of youth after program implementation. The Mann Whitney U test was used to analyze the differences between each of the seven components between the two groups. The study however, showed that there were no significant differences between the two groups in all components of soft skills after program implementation. The research findings provide some information for researchers to redefine the contents and the duration of youth development program to ensure that the objectives of such program can be achieved.